2018
DOI: 10.1111/tpj.14009
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of genome‐wide recombination rate variation in allopolyploid wheat revealed by nested association mapping

Abstract: SummaryRecombination affects the fate of alleles in populations by imposing constraints on the reshuffling of genetic information. Understanding the genetic basis of these constraints is critical for manipulating the recombination process to improve the resolution of genetic mapping, and reducing the negative effects of linkage drag and deleterious genetic load in breeding. Using sequence‐based genotyping of a wheat nested association mapping (NAM) population of 2,100 recombinant inbred lines created by crossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 73 publications
4
125
3
Order By: Relevance
“…As expected, pairwise LD is consistently higher in peri‐centromeric regions (Figure b), even though markers are preferentially located in telomeric regions (Figure S7). These results are in agreement with the recombination frequency distribution observed in a bread wheat NAM (Jordan et al ., ). It is likely that the areas of high LD around centromeres are more extensive then what is apparent using the current marker set.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As expected, pairwise LD is consistently higher in peri‐centromeric regions (Figure b), even though markers are preferentially located in telomeric regions (Figure S7). These results are in agreement with the recombination frequency distribution observed in a bread wheat NAM (Jordan et al ., ). It is likely that the areas of high LD around centromeres are more extensive then what is apparent using the current marker set.…”
Section: Discussionmentioning
confidence: 97%
“…The EtNAM will side the multiparental populations available (Milner et al, 2016;Huang et al, 2012;Jordan et al, 2018;Mackay et al, 2014) and those in development in the Triticum species complex. It has been shown that the parallel employment of NAM families developed in closely related species can reinforce QTL findings (Mace et al, 2013), increasing their potential use in breeding efforts.…”
Section: The Etnam As a Qtl Mapping And Pre-breeding Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…We can now use this knowledge to break these negative correlations by purposely generating haplotypes that combine both beneficial traits. This will be facilitated by ongoing studies into the genetic basis of recombination in wheat, which could provide the knowledge to manipulate recombination rate distribution across chromosomes (Jordan et al ., ). With clearly defined haplotypes, we can also leverage the multiple layers of genomic information (e.g.…”
Section: Moving From Snps To Haplotypes In Breedingmentioning
confidence: 97%
“…Much of this variation is studied through genetic populations composed of cultivars that differ for the trait(s) of interest. These include bi‐parental populations between two cultivars (Saintenac et al ., ), multi‐parent advanced generation inter‐cross (MAGIC) populations composed of between 4 and 16 cultivars (Huang et al ., ; Mackay et al ., ; Milner et al ., ; Dixon et al ., ), nested association mapping panels of multiple cultivars to a common parent (Jordan et al ., ), and association panels of 100 or more cultivars (Sukumaran et al ., ; Liu et al ., ). All of these types of populations are available in wheat and their relative merits are discussed elsewhere (Huang and Han, ).…”
Section: Use Of Natural Variation For Trait Discoverymentioning
confidence: 99%